Determination of Growth Inhibitory Effect of Gemcitabine on Human Intrahepatic Cholangiocarcinoma Cell lines and Comparison of its Inhibition Between the Generic and Reference Formulation - Dokduang, Hasaya; Namwat, Nisana; Jusakul, Apinya; Bhudisawadi, Vajarabhongsa; Loilome, Watcharin; Yongvanit, Puangrat; Sripa, Banchob; Tassaneeyakul, Wichittra (Srinagarind Medical Journal, 2013)
Background and Objective: Gemcitabine is one of the most popular drug-of-choices that is currently used for the treatment of cholangiocarcinoma (CCA). However, the study revealing the inhibitory effect of this agent in the series of CCA cell lines established from Thai patients has not been reported. We aim to determine and compare the growth inhibitory effect of generic gemcitabine formulation with the reference formulation on CCA cell lines. Methods: Seven CCA cell lines established in Srinagarind Hospital, Khon Kaen University were used. A cell growth inhibition by gemcitabine was determined by sulforhodamine B. The IC50 value was expressed as the concentration of drug that caused a 50% growth inhibition comparing with untreated control. The IC50 values of those two formulations were compared using independent t-test. Results: Growths of KKU-M055, KKU-OCA17 and KKU-M139 CCA cell lines were highly inhibited by gemcitabine (IC50 = 13.35-16.0 mM) whereas KKU-M214 was moderately inhibited by this drug (IC50 = 36.7 mM). These least inhibited growths were found on KKU-100, KKU-M156 and KKU-M213 (IC50 = 406-4629 mM). The generic (GramagenÒ) and the reference product (GemzaÒ) formulations were not significantly different in their inhibitory effects on the all seven CCA cell lines. Conclusions: Although the inhibitory effect of gemcitabine was varied towards seven CCA cell lines, there was no difference in the IC50 values of the generic and reference formulations. Our findings indicate that the in vitro efficacy of these two formulations is similar. Keywords: growth inhibitory effect, gemcitabine, cholangiocarcinoma, generic formulation